2002
DOI: 10.1038/sj.onc.1205026
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of altered TGF-β expression and responsiveness in breast cancer: evidence for autocrine and paracrine effects

Abstract: To characterize the impact of increased production of TGF-b in a xenograft model of human breast cancer, TGF-b-responsive MDA-231 cells were genetically modi®ed by stable transfection so as to increase their production of active TGF-b1. Compared with control cells, cells that produced increased amounts of TGF-b proliferated in vitro more slowly. In vivo, however, tumors derived from these cells exhibited increased proliferation and grew at an accelerated pace. To evaluate the role of autocrine TGF-b signaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…Tobin et al, (2002) observed a marked enhancement of tumour growth in vivo by tumour-derived TGF-b when an autocrine loop was left intact. Studies also found that increased production of TGF-b1 by tumour cells was associated with potential invasiveness and metastasis of cancer (Gorsch et al, 1992;Dalal et al, 1993;Ueki et al, 1993;Tobin et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Tobin et al, (2002) observed a marked enhancement of tumour growth in vivo by tumour-derived TGF-b when an autocrine loop was left intact. Studies also found that increased production of TGF-b1 by tumour cells was associated with potential invasiveness and metastasis of cancer (Gorsch et al, 1992;Dalal et al, 1993;Ueki et al, 1993;Tobin et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Studies of TGF-b1 signal transduction provided further evidence that low expression of TbRII by breast cancer cells was correlated with enhanced in vivo malignant behaviours both in tumour specimens and a cancer cell line (Gobbi et al, 1999). Tobin et al, (2002) observed a marked enhancement of tumour growth in vivo by tumour-derived TGF-b when an autocrine loop was left intact. Studies also found that increased production of TGF-b1 by tumour cells was associated with potential invasiveness and metastasis of cancer (Gorsch et al, 1992;Dalal et al, 1993;Ueki et al, 1993;Tobin et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…These include tubulin alpha 3, which has been previously found to be overexpressed in malignant breast tumours immunohistochemically 160 Transforming growth factor beta 1, a multifunctional peptide that controls proliferation and differentiation, was also upregulated 2.15 fold in the IGF-1 positive tumours 161 . In addition it has been shown to promote the formation of lung metastases in animal models of breast cancer 161 . We also found an over expression of carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM 1)…”
Section: Microarraymentioning
confidence: 94%
“…Overexpression of TGF-b was observed in tumors in association with metastasis (Kopp et al, 1995) or increased cell invasiveness (Tobin et al, 2002;Dumont et al, 2003). An important function related to promotion of metastasis is the phenomenon of EMT.…”
Section: Introductionmentioning
confidence: 99%